Witness for the Defense: A Right to Immunity - Mass, Robin D. (1981)
This Note has outlined various constitutional arguments that the criminal defendant can invoke in support of an application for witness immunity.First, the Note relies on the Supreme Court's decision in United States v. Nixon for its argument that courts should use a flexible separation of powers approach in the context of witness immunity grants. While the Nixon Court accepted the notion that separation of powers protects the decision making authority of the individual branches of government from infringement by the other branches, it observed that the doctrine does not enforce an absolute executive privilege. Thus, the separation of powers doctrine need not preclude judicial review of executive discretion in all circumstances. The Court also stressed that the defendant's need to obtain all relevant evidence should outweigh a general claim of executive privilege in a criminal trial. Thus, Nixon is persuasive authority for the position that courts should willingly review discretionary actions of the prosecutor. Second, this Note considers the feasibility of initiating a due process claim when the government denies a request for defense witness immunity. The holdings of Brady and Roviaro exemplify the great weight traditionally accorded the defendant's need for evidence. The doctrine of reciprocal discovery lends further credence to the proposition that the defense should have immunity grants available to it and that such immunity should not be dependent on the government's decision to immunize one of its own witnesses. The change in the scope of protection from transactional to use immunity has significantly reduced the weight accorded the government's interests in denying immunity to a defense witness.Although the prosecutor may occasionally encounter added inconvenience when he later attempts to prosecute an immunized defense witness, the added costs may be adequately minimized so that the burden on the government is substantially reduced. Finally, the change to use immunity also reduced the weight given to the witness' interest. The immunized witness' interest is now limited to protection from use or derivative use of his compelled testimony in a subsequent criminal case. Thus, a balancing of the three interests at stake when the defense requests witness immunity indicates that the due process analysis often constitutes a convincing argument in favor of an award of immunity